Engineering behaviour of artificially cemented sand : cement treatment versus biocement treatment - Wang, Lei (Nanyang Technological University, 2021)
The engineering properties of soil can be enhanced through artificial cementation which is realized by premixing or injecting chemical agents such as cement, lime and gypsum in soil. Biocementation of soil using biogenic cements has also been developed in recent years.